429. DETECTION OF MOLECULAR RESIDUAL DISEASE (MRD) USING MATCHED TUMOR-MARGIN SEQUENCING IN EARLY STAGE ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (24th September 2022) - Lu, Di; Tong, Yu; Zhai, Jianxue; Wang, Zhizhi; Chen, Zhiming; Wu, Hua; Li, Shaobin; Cai, Kaican
Abstract: Residual disease is one of the main sources of recurrence in post-surgical esophageal squamous cell carcinoma (ESCC). However, the prognostic value of histologically-defined surgical margin status is limited by its suboptimal accuracy in indicating patients' outcomes. Here, we explored the potential of margin-molecular residual disease (MRD) based on next-generation sequencing (NGS) as a feasible and more reliable biomarker for identifying patients with a high risk of recurrence. NGS data from 22 early stage ESCC patients with matched tumor and histologically negative resection margin, as well as normal epithelial tissue samples, were retrospectively reviewed. Comparisons of the respective mutational landscapes, as extracted by profiling using a 425-cancer-gene panel (GeneseeqPrime®), were performed. Associations of disease-free survival (DFS) with clinical features and margin-MRD were analyzed. A total of the 11 (50%) patients with histologically negative margin had detectable somatic mutations as assessed by NGS. TP53 alterations were highly enriched in the tumor (ptumor-normal = 0.001) and the margin (pmargin-normal = 0.015) samples compared with the normal tissues, whereas NOTCH1 alterations were much more common in the normal samples (ptumor-normal = 0.001, pmargin-normal = 0.001). Tumor-specific mutations were detected in six (6/11, 55%) of the NGS-positive margins. Survival analysis showed that those having MRD-positive margins had an unfavorable DFS compared with those having MRD-negative margins (p = 0.08, HR (95%CI): 3.28 (0.81–13.4)). In this study, the presence of mutations in a considerable proportion of histologically negative resection margins and a tendency for worse prognosis in patients carrying MRD-positive margins was demonstrated. Our findings suggest that margin-MRD may serve as a more accurate prognostic predictor for disease recurrence, and highlight the clinical relevance of using NGS to detect MRD for proper prognostic stratifications and precise treatment guidance.